1997
DOI: 10.1152/ajpendo.1997.272.3.e390
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of prolactin gene transcription, mRNA storage, and hormone release in individual mammotropes

Abstract: The mammotrope has traditionally been a favored model for studies of hormonal gene expression, biosynthesis, and release. However, the primary site(s) at which these processes are coordinated and integrated remains to be established. Because there is considerable indirect evidence to suggest that the rate of prolactin (PRL) secretion is dictated, in large part, at the level of transcription, the relative contribution of other putative regulatory foci has received less attention. The purpose of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…In this scenario, a particular series of [Ca 2ϩ ] i oscillations would act over the short term to evoke hormone release and over the long term to induce gene expression required for replenishment of hormonal stores. Our recent observation on the dissociation between PRL gene transcription, mRNA storage, and hormone release within the same mammotropes is entirely consistent with this possibility (25).…”
Section: Discussionsupporting
confidence: 79%
“…In this scenario, a particular series of [Ca 2ϩ ] i oscillations would act over the short term to evoke hormone release and over the long term to induce gene expression required for replenishment of hormonal stores. Our recent observation on the dissociation between PRL gene transcription, mRNA storage, and hormone release within the same mammotropes is entirely consistent with this possibility (25).…”
Section: Discussionsupporting
confidence: 79%
“…This lack of correspondence between RNA and protein levels is not surprising and has been already described (Salari et al 2012, Beileke et al 2015. One study specifically evidenced the mismatch between the prolactin mRNA expression and hormone release (Castaño et al 1997). Thirdly, we demonstrated that adiponectin downregulates IGFBP-1 and connexin-43 mRNA expression levels.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, it was noted that both P. gingivalis LPS 1435/1449 and E. coli LPS significantly upregulated the expression of MMP-2 mRNA but not its protein as compared to the controls. A number of factors may account for this finding, such as the stability of mRNA, its processing and splicing patterns, half-life of the target protein and post-translational modifications [43,44]. Therefore, in the present study increase in MMP-2 mRNA expression level may not be necessarily reflected at its protein level.…”
Section: Discussionmentioning
confidence: 72%
“…Based upon the current findings, further study may be warranted to explore the association of different isoforms of P. gingivalis LPS with periodontal conditions in periodontal patients and the possible effect of periodontal treatment on the expression of these LPS isoforms by P. gingivalis . In addition, the discrepancy observed in TIMP-1 mRNA and protein expression following the stimulation of both P. gingivalis LPS 1435/1449 and E. coli LPS in HGFs could be due to the complex regulation of transcription and translation [43,44]. …”
Section: Discussionmentioning
confidence: 99%